All poly(3, 4-ethylenedioxythiophene) organic electrochemical transistor to amplify amperometric signals. (1st April 2018) - Gualandi, I.; Scavetta, E.; Mariani, F.; Tonelli, D.; Tessarolo, M.; Fraboni, B.
Abstract: Organic Electrochemical Transistors (OECTs) are emerging devices that find applications as sensors because they offer amazing features such as intrinsic signal amplification, low energy consumption, low cost and easy adaptability to new and unconventional architectures. The signal transduction usually exploits a redox reaction as happens in a common amperometric sensor, but the channel of the transistor is able to amplify this signal. This paper aims to thoroughly investigate the amplification of Faradaic currents in OECT sensors that exploit PEDOT:PSS (poly(3, 4-ethylenedioxythiophene):poly (styrene sulfonate)) as semiconductor material in the channel and electrochemical transducer. The devices were fabricated with different geometries and thicknesses of PEDOT:PSS in order to find the best configuration. The amplification was studied in phosphate buffer solution as electrolyte by determining the OECT transconductance. A thick PEDOT:PSS layer and a high ratio between gate and channel areas ensure the best performance from an electrical point of view. The amplification was also studied while the OECTs work as chemical sensors for the detection of ascorbic acid. The highest gain was observed for the thickest PEDOT:PSS channel and the lowest ratio between the gate and the channel areas. Moreover, the gate voltage has an important effect on the transistor amplification, being the gain highest (of about 2 orders of magnitude) for the lowest gate voltage. Graphical abstract: